Behavioral and neurophysiological evidence for increased cognitive flexibility in late childhood - Wolff, Nicole; Roessner, Veit; Beste, Christian (Scientific reports, 2016)
Executive functions, like the capacity to control and organize thoughts and behavior, develop from childhood to young adulthood. Although task switching and working memory processes are known to undergo strong developmental changes from childhood to adulthood, it is currently unknown how task switching processes are modulated between childhood and adulthood given that working memory processes are central to task switching. The aim of the current study is therefore to examine this question using a combined cue- and memory-based task switching paradigm in children (N = 25) and young adults (N = 25) in combination with neurophysiological (EEG) methods. We obtained an unexpected paradoxical effect suggesting that memory-based task switching is better in late childhood than in young adulthood. No group differences were observed in cue-based task switching. The neurophysiological data suggest that this effect is not due to altered attentional selection (P1, N1) or processes related to the updating, organization, and implementation of the new task-set (P3). Instead, alterations were found in the resolution of task-set conflict and the selection of an appropriate response (N2) when a task has to be switched. Our observation contrasts findings showing that cognitive control mechanisms reach their optimal functioning in early adulthood.
Keywords: vývoj člověka; exekutivní funkce; Memory; lidé; mladiství; mužské pohlaví; mladý dospělý; Human Development; paměť; Young Adult; ženské pohlaví; neuropsychologické testy; Humans; pozornost; Attention; Executive Function; Female; Adolescent; Neuropsychological Tests; Male